Design of Mine-Detecting Robot Using Yolov8 Object Detection Model - Karpenko, А. (ХНУРЕ, 2025)
Methods of developing a demining robot, based on Android application control and YOLOv8 image detection algorithm, are uncovered in this article
Keywords: computer vision; demining; explosives; landmine; object detection; robot; MIT App Inventor; YOLOv8